Padrões de fenologia foliar e a vulnerabilidade ao embolismo em uma floresta de terra firma na Amazônia Central - Pinho, Davieliton Mesquita (Instituto Nacional de Pesquisas da Amazônia - INPA, 2021)
We analyzed photographic images taken from the top of a tower (80m) at the ATTO site to understand the leaf change pattern of 267 trees over five years. Additionally, we measured xylem vulnerability to cavitation in a subsample of these trees. We found that 16% of the trees show brevidecidual behavior, 36% are evergreen with massive leaf shedding and 30% are evergreen without massive leaf shedding. A small group of trees release new leaves during the rainiest months of the year, however they do not repeat the same behavior in different years. We observed that there are two peaks of leaf release during the six driest months of the year. The two peaks are made up of distinct phenological groups, the evergreen ones with leaf renewal at the beginning of the months with less rainfall and the brevideciduous ones producing leaves in the middle of the dry period. Finally, we found a relationship between the time for leaf renewal, phenological groups (i.e., evergreen and brevidecidus) and xylem vulnerability to cavitation.
Keywords: Fenologia Foliar; Grupos fenológicos; Embolismo; Amazônia Central